Conformal skin bioelectrodes - Li, Wenlong (Nanyang Technological University, 2022)
Human beings leverage electrical signals to modulate their physiological activities. The electrical signals generated from neural cells, skeletal and cardiac muscle fibers can be transmitted through the human body and summed up as biopotential changes which can be measured from the skin. Depending on the generation source, the biopotential signals can be classified as the electrocardiogram (ECG, from the heart), electromyogram (EMG, from skeletal muscle), electroencephalogram (EEG, from brain neural activity), etc. The measurement of such biopotential signals presents a vital diagnostic tool in clinical practices. The on-skin detection of biopotential signals depends on skin electrodes that transduce ionic current in human tissue into electronic current for external amplifier pickup. The commercial skin electrodes used in clinics are Ag/AgCl bulk metal electrodes with adhesive gel pasted on them. The Ag/AgCl-gel electrodes are fixed by medical tape on the skin. Such commercial skin electrodes present some critical shortcomings. One is that the bulky electrode cannot be stretched to accommodate the easily deformed skin, resulting in artifacts and hindrance of body movements during the measurement. The other is that the electrode relies on medical tape for fixation, which would cause discomfort or even skin trauma when peeling off the tape. In this regard, skin electrodes that are stretchable, soft, and comfortably adhesive are needed. This thesis explores the novel skin bioelectrode solutions from a materials design perspective. Adhesive hydrogels that are highly stretchable (strain >300%), soft (Young’s modulus < 100 kPa), and conductive are fabricated as skin-contacting layers for electrodes application. The optical, mechanical, and electrical properties can be further enriched by ionic additives. In addition, antimicrobial properties can be introduced into the hydrogel materials by a novel co-assembly of silk fibroin with Fmoc-protected amino acids. The antimicrobial hydrogel material for skin electrodes can effectively prevent skin inflammation and biofilm formation. Furthermore, ultrathin Au nanomesh material as an electronic conductor is chemically synthesized to transduce the ionic current in hydrogel into the electronic current. The Au nanomesh, formed from intertwined Au nanowires, is electronically conductive and optically transparent. It can be transfer-printed on stretchable substrates and adhered to hydrogel to form skin electrodes. Lastly, to overcome the fast-drying issue of hydrogels as soft skin adhesive, a universal adhesive coating technique is also introduced for long-term comfort skin adhesion. Such a coating technique can be applied to most of the non-adhesive stretchable electrodes without deteriorating their electronic conductivity. These conformal skin electrodes allow high fidelity biopotential signal measurement from the skin without causing skin discomfort.